Limnology The Importance of Monitoring and Correlations of Lentic and Lotic Waters - Massarelli, Carmine; Campanale, Claudia (Environmental Sciences, 2023)
The book includes important contributions that discuss state-of-the-art techniques and technologies for monitoring lentic and lotic water environments. It includes contributions that deepen and integrate the knowledge of the impacts and pressures of surrounding environments in the monitoring techniques of aquatic environments. Furthermore, the book presents studies relating to the management of inland waters and related indicators to identify the most common pollution problems.